The epidemiology of injuries in club rugby in Namibia - Morkel, Vernon (University of the Free State, 2016)
Background: Several studies have reported the epidemiology of injuries in professional rugby union, but there are limited studies about amateur rugby, especially in a third-world setting. No epidemiological studies have been done on injuries in Namibian club rugby. Namibian rugby does not have an injury prevention programme, so the expectation is that there is a high rate of injuries and recurrent injuries in Namibian rugby. Aims: The aim of the study was to investigate the epidemiology of injuries among club rugby players in Namibia, with specific reference to recurrent injuries. The ultimate goal will be to use the results of this study to develop an injury prevention programme for Namibian rugby. Method: A prospective, descriptive study was undertaken to investigate the injury epidemiology among the players of 11 Namibian premier league rugby teams. Of the 414 players who played in premier league matches, 117 players suffered 156 injuries. The researcher visited all 11 clubs to collect the data from the injured players. The researcher conducted telephone interviews with the players who were not personally interviewed. All data were recorded on data collection forms, and the date included the players’ anthropometric data, dates of injuries and return from injury, time the match injury occurred, match event causing the injury, body location of injury, diagnostic investigations done and treatment received and whether the injury was recurrent. Results: The injury rate of time-loss injuries in matches was 74.4 injuries per 1 000 player-match hours for the season. Most injuries (87.7%) took more than seven days to recover from, which is longer than expected. Most injuries (34.4%) occurred during the final quarter of a match. The tackle was responsible for most (48.4%) of all time-loss injuries and all contact match events caused 83.5% of all match injuries. Significantly more running injuries (12.3% or 9.1 per 1 000 player-match hours) were recurrent than first-time injuries (5.7% or 4.3 per 1 000 player-match hours) (p=0.05). Backline players (44.5 injuries per 1 000 player-match hours) had more injuries than forwards (29.9 injuries per 1 000 player-match hours), with the highest injury incidence among inside backs (scrumhalf, flyhalf and centre positions) (23.8 injuries per 1 000 player-match hours). Most injuries (78.2%) were match injuries, compared to only 21.8% training injuries. The most frequent anatomical sites for injury in this amateur club league were the ankle (17.3% of all injuries), hamstring muscle (16.7%), knee (15.4%) and shoulder (15.4%). Concussion accounted for only 4.5% of all injuries. Of the total 156 injuries in this study 76 were recurrent injuries, meaning that 48.7% of all the injuries were recurrences of previous injuries. It is the highest recurrent injury rate reported to date in rugby union. Conclusions: The injury rate is very high, compared to other amateur club settings. Injuries are, on average, much more severe in this league than in other amateur and professional leagues. The incidence of recurrent injuries is significantly more than has ever been reported for rugby union. This high injury burden may be due to the lack of an official injury prevention programme in Namibian rugby. The results of this study can be used to introduce an injury prevention programme for Namibian rugby.
Dissertation (M.Sports Med. (Sports Medicine))--University of the Free State, 2016
Keywords: Injury incidence; Injury severity; Recurrent injury; Injury prevention; Amateur rugby; Premier league; Namibia rugby; Football injuries -- Namibia